Strategi Pengembangan Agribisnis Muntok White Pepper dengan Business Model Canvas (BMC) (Studi Kasus di Muntok White Pepper (MWP) Agrotourism Edupark) - Paramitha, Annisa Pradnya; Agustina, Fournita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Muntok White Pepper farming as a commodity with Geographical Indications (GI) from the Province of Bangka Belitung Islands is showing decline, so that agribusiness development is needed to restore the glory of Muntok White Pepper in supporting the public's economy. The purpose of this research were (1) Analyzing the determinants of white pepper agribusiness development decisions; and, (2) Developing alternative strategy of white pepper agribusiness development using Business Model Canvas (BMC) in Air Gegas Subdistrict, South Bangka District. This research was conducted at Muntok White Pepper (MWP) Agrotourism Edupark in Nyelanding Village, Air Gegas Subdistrict, South Bangka District from February 2023 to July 2023 using the case study method. The data used in this research were primary data and secondary data that collected through observation, interview, questionnaire, and library study. The primary data came from sample selected using purposive sampling in the form of white pepper farmers who initiated the development of Muntok White Pepper (MWP) Agrotourism Edupark, meanwhile the secondary data came from theory and previous research. These data were analyzed using qualitative research method. The results of this research indicated that (1) The determinants of white pepper agribusiness development decisions of Muntok White Pepper (MWP) Agrotourism Edupark in Air Gegas Subdistrict consist of three research variables, including age, level of formal education, farming experience; and, (2) The priority alternative strategy of white pepper agribusiness development of Muntok White Pepper (MWP) Agrotourism Edupark in Air Gegas Subdistrict composed of nine elements in Business Model Canvas (BMC) is the expansion through promotion on social media as proof of the success of GAP and GHP implementation.